Socialization of Taxes and Financial Reporting to MSME Bazar Participants - Refi Pratiwi; Intan Puspanita; Asih Machfuzhoh; Selly Anggraeni Haryono (EQUATOR SINAR AKADEMIA, 2023)
MSMEs have the potential to improve the implementation of their tax obligations. However, due to weak access to information by MSMEs, in general they do not necessarily understand and comprehend the benefits of fulfilling tax obligations. In the bazaar activity, which was attended by 37 students, some of the teams were business people who actually had businesses while studying, the team assistants and lecturers socialized the importance of taxes to entrepreneurs, they were given an understanding of taxation since they were in college and not only got the theory but in practice these business people were the ones who dominated by students must understand. The process of how business actors get a NPWP which will change their tax identity using a Resident Identity Card. Not only understanding taxation, but in this activity students and business people are also asked to understand the financial reports that must be made after the activity is completed.This activity was carried out at a bazaar event with 37 teams taking part in this activity consisting of 3 students. The aim of this service is to provide an understanding of taxation and financial reports. Business people understand taxation and financial reports.